HERMENEUTIKA JORGE J.E. GRACIA SEBAGAI ALTERNATIF TEORI PENAFSIRAN TEKSTUAL ALQUR’AN - Syamsul Wathani (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2017)
This article discusses the Jorge J.E. Gracia’s hermeneutical concept used as an alternative theory of the Qur’anic textual interpretation. The discussion focuses on three main points, (i) the Qur’anic textual narration as the object of interpretation, (ii) Gracia’s hermeneutic to interpret the text, and (iii) arranging the Qur’anic textual interpretation paradigm. Based on the interpretive study, started with mapping Gracia's theory of understanding, and then systematizing it into the theory formulation, the results of the study showed: (1) the concept of qur'anic text (alnash) is the ultimate consciousness. The Qur'an is something readable/touchable (almaktub). As an alnash, Qur'an has a text mechanism in which its contextual approach becomes the main gate to open its meaning. (2) The Gracia's hermeneutic logical reasoning is directed to overcome misunderstanding (not understanding) of the text. While the development of textual interpretation method used to bridge between the historical text and the audience’s situation. (3) The paradigm of the textual interpretation used as a worldview to look at the Qur'an and its interpretation, with the concept of "alnash" as its starting point, and then working with emphasizing the existing understanding among text, audience, and context.